2003
DOI: 10.1038/sj.ijir.3900996
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Brief Male Sexual Inventory in community men

Abstract: The objectives of the study were to characterize male sexual functioning as related to age in community-dwelling older men. In 1989, a random sample of men aged 40-79 y (n ¼ 2115) without prior prostate surgery, prostate cancer, or other conditions known to affect voiding function (except benign prostatic hyperplasia) was invited (55% agreed) to participate in the Olmsted County Study of Urinary Symptoms and Health Status Among Men. In 1996, a previously validated male sexual function questionnaire was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 16 publications
7
52
0
2
Order By: Relevance
“…[29,30] The BMSFI was developed as a validated way to characterize sexual function by clinicians and researchers. [31] Dinçer et al [13] used the BMSFI scale and found that all of its domains, except for the ejaculation domain, were significantly lower in male patients with AS compared with healthy controls. Özkorumak et al [14] used the GRISS scale and evaluated 43 male patients with AS and found that the frequency of sexual dysfunction was significantly higher in these patients than for the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] The BMSFI was developed as a validated way to characterize sexual function by clinicians and researchers. [31] Dinçer et al [13] used the BMSFI scale and found that all of its domains, except for the ejaculation domain, were significantly lower in male patients with AS compared with healthy controls. Özkorumak et al [14] used the GRISS scale and evaluated 43 male patients with AS and found that the frequency of sexual dysfunction was significantly higher in these patients than for the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we only used two questions on sexual satisfaction and erection difficulty. Although many other studies used a single question 2,25 or multiple questions 23,26 to measure ED, future studies should use the International Index of Erectile Function (IIEF) questionnaire (IIEF-15 27 or IIEF-5 17 ) to allow for standardized comparison across studies.…”
Section: Discussionmentioning
confidence: 99%
“…La fiabilidad test-retest, con una semana de intervalo, fluctuó entre 0,79 y 0,89. El BSFI mostró además una adecuada validez discriminante por grupos de edad (O'Leary et al, 1995(O'Leary et al, , 2003. Posteriormente, Mykletun, Dahl, O´Leary y Fossa (2005) plantean una estructura trifactorial (Impulso, Erección y Eyaculación), una vez descartados los ítems referidos a problemas y satisfacción; esta solución llega a explicar el 87% de la varianza.…”
Section: Introductionunclassified